Bimodal effect of hydrogen peroxide and oxidative events in nitrite-induced rapid root abscission by the water fern Azolla pinnata - Cohen, Michael F.; Gurung, Sushma; Birarda, Giovanni; Holman, Hoi-Ying N.; Yamasaki, Hideo (Frontiers in Plant Science, 2015)
In the genus Azolla rapid abscission of roots from floating fronds occurs within minutes in response to a variety of stresses, including exposure to nitrite. We found that hydrogen peroxide, though itself not an inducer of root abscission, modulates nitrite-induced root abscission by Azolla pinnata in a dose-dependent manner, with 2 mM H2O2 significantly diminishing the responsiveness to 2 mM NaNO2, and 10 mM H2O2 slightly enhancing it. Hypoxia, which has been found in other plants to result in autogenic production of H2O2, dramatically stimulated root abscission of A. pinnata in response to nitrite, especially for plants previously cultivated in medium containing 5 mM KNO3 compared to plants cultivated under N2-fixing conditions without combined nitrogen. Plants, including Azolla, produce the small signaling molecule nitric oxide (NO) from nitrite using nitrate reductase. We found Azolla plants to display dose-dependent root abscission in response to the NO donor spermine NONOate. Treatment of plants with the thiol-modifying agents S-methyl methanethiosulfonate or glutathione inhibited the nitrite-induced root abscission response. Synchrotron radiation-based Fourier transform infrared (SR-FTIR) spectromicroscopy revealed higher levels of carbonylation in the abscission zone of dropped roots, indicative of reaction products of polysaccharides with potent free radical oxidants. We hypothesize that metabolic products of nitrite and NO react with H2O2 in the apoplast leading to free-radical-mediated cleavage of structural polysaccharides and consequent rapid root abscission.